Analysis Of Student’s Response Toward Online Learning System Based On Academic Intensive-Home Activity - Sulhairi; M Saleh Yahya Himni; Bayu Islam Assasaki (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2022)
The implementation of online learning has the potential to be a challenge for education practitioners to carry out learning and teaching activities. Online learning systems tend to have a different reciprocal impact than face-to-face learning. This condition is certainly a difficulty for educators in carrying out online learning and teaching. The increasing online learning platforms indirectly change the set of lecturers to be more open-minded and inclusive of a variety of renewable information technologies that can support the sustainability of the teaching and learning process. The focus of this study generally was; 1) To analyze the student’s responses to an online learning system based on academic intensive home activities; 2) To analyze the effectiveness of the online learning system during the pandemic. The purpose of this study was to analyze the student's responses to the online learning system based on academic intensive-home activity. The method was qualitative descriptive research. The results of this study were; that 75% of the online learning process was based on doing academic homework intensively. 66.7% of students were motivated by an online learning system based on academic intensive-home activities. 85.5% of student performance improved in literacy and digital literacy.